Teacher AfL perceptions and feedback practices in mathematics education among secondary schools in Tanzania. (December 2018) - Kyaruzi, Florence; Strijbos, Jan-Willem; Ufer, Stefan; Brown, Gavin T.L.
Highlights: 54 Year 11 (Form three) mathematics teachers in 48 Tanzanian schools surveyed and interviewed. Teachers evaluated positively their own FA, AfL, and feedback practices. Assessment conceptions and practice perceptions predicted 58% of variance of feedback practices. Teachers reported to use students' assessment information for formative and summative purposes. Abstract: Feedback that monitors and scaffolds student learning has been shown to support learning. This study investigates the effect of mathematics teachers' perceptions of Formative Assessment (FA) and Assessment for Learning (AfL) and their conceptions of assessment on the quality of their feedback practices. The study was conducted in 48 secondary schools in Tanzania with 54 experienced mathematics teachers teaching Grade 11 (Form three in the Tanzanian system). Validated questionnaires were combined with interviews to investigate mathematics teachers' perceptions, conceptions, and feedback practices. Data were analysed by structural equation modeling and content analysis techniques. Results from the structural equation model indicated that mathematics teachers' perceptions of FA and AfL and their conceptions of assessment purposes positively predicted the quality of their feedback practices. Interview results illustrated that mathematics teachers used their students' assessment information for both formative and summative purposes. Future interventions for improving the quality of mathematics teacher's feedback practices are proposed.